2005
DOI: 10.1002/ajmg.b.30135
|View full text |Cite
|
Sign up to set email alerts
|

Serotonin transporter promoter polymorphism and monoamine oxidase type A VNTR allelic variants together influence alcohol binge drinking risk in young women

Abstract: The short allelic variant of the serotonin transporter protein promoter polymorphism (5HTTLPR) appears to influence binge drinking in college students. Both monoamine oxidase type A (MAOA) and the serotonin transporter protein are involved in the processing of serotonin, and allelic variants are both associated with differences in the efficiency of expression. We hypothesized that a significant gene x gene interaction would further stratify the risk of binge drinking in this population. Participants were colle… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
38
0

Year Published

2005
2005
2015
2015

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 40 publications
(42 citation statements)
references
References 20 publications
4
38
0
Order By: Relevance
“…In the current study, SS subjects tended to drink more and to be of a younger current age than LL subjects, which is consistent with the finding of Herman et al (2005) that binge drinking may be greater in young college-aged adults with the SS genotype. However, the current study found no significant relationships between 5-HTT genotype and age of onset of alcoholism, which is consistent with family-based studies reporting no differential association of the L or S allele with early onset of alcoholism in offspring (Samochowiec et al, 2006).…”
Section: Discussionsupporting
confidence: 91%
“…In the current study, SS subjects tended to drink more and to be of a younger current age than LL subjects, which is consistent with the finding of Herman et al (2005) that binge drinking may be greater in young college-aged adults with the SS genotype. However, the current study found no significant relationships between 5-HTT genotype and age of onset of alcoholism, which is consistent with family-based studies reporting no differential association of the L or S allele with early onset of alcoholism in offspring (Samochowiec et al, 2006).…”
Section: Discussionsupporting
confidence: 91%
“…A study was designed by Herman et al 83 to examine the gene--gene (GxG) interaction between the functional polymorphism in the promoter region of the 5HTTLPR and the MAOA-mVNTR polymorphism related to binge drinking behavior in college females. Interestingly, the highest risk was found in homozygous for the short variant allele of the 5HTTLPR (SS) in combination with the higher activity forms of the MAOA-mVNTR (HH) (OR = 3.11, 95% CI = 1.14-18.10), and the lowest risk was found in individuals carrying at least one long variant of the 5HTTLPR (LL or LS) in combination with higher activity MAOA-mVNTR alleles (HH) (OR = 0.46, 95% CI = 0.28-0.71) 83 .…”
Section: Alcohol Dependencementioning
confidence: 99%
“…Herman et al (2005) also reported that the S allele was associated with a higher risk for binge drinking among women. Hammoumi et al (1999) showed that Caucasian subjects with the SS and SL genotypes had increased frequency of binge drinking, compared to the LL genotype.…”
Section: -Httlpr Polymorphism and Alcohol Use Problemsmentioning
confidence: 95%
“…Matsushita et al (2001) reported a higher frequency of the SS genotype among a sub-group of Japanese male adult alcoholics with binge drinking behaviors. Herman et al reported an association between the S allele and alcoholism in young Caucasian women (Herman et al 2005). Hallikainen et al (1999) found that the S allele was associated with early onset alcoholism in a Finnish study.…”
Section: -Httlpr Polymorphism and Alcohol Use Problemsmentioning
confidence: 98%
See 1 more Smart Citation